MicroRNA let-7a inhibits proliferation of breast cancer cell by downregulating USP32 expression - Liu, Chunyan; Chen, Zhaobo; Fang, Min; Qiao, Yun (Translational Cancer Research, 2019)
Background: The present study aimed to investigate the effect of microRNA (miR) let-7a on ubiquitin specific protease 32 (USP32) expression and its potential function in MCF-7 breast cancer (BCa) cell line. Methods: BCa MCF-7 cells were transfected with hsa-miR let-7a mimics or inhibitors, then the USP32 expression was evaluated using quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot analysis in the transfected cells. USP32 as a target regulated by miR let-7a was confirmed via Dual-luciferase reporter assay. The effects of miR let-7a on the viability were determined using MTT assay and colony formation analysis. Results: Western blot analysis revealed that miR let-7a mimics dramatically decreased the USP32 protein expression, whereas miR let-7a inhibitors increased the protein expression of USP32 compared with their controls in the MCF-7 cells. Dual-luciferase reporter assay showed that miR let-7a mimics could directly target the 3'-untranslated region (UTR) of USP32. Further, MTT assay and colony formation analysis showed that miR let-7a significantly inhibited cell proliferation of MCF-7 cells. However, overexpression of USP32 could reverse the effect of miR let-7a on MCF-7 cells proliferation. Conclusions: Collectively, the results suggested that miR let-7a functions as a tumor suppressor to reduce proliferation by targeting USP32 in BCa cells.